Synthesis, cytotoxicity in vitro, apoptosis, cell cycle arrest and comet assay of asymmetry ruthenium(II) complexes. (26th February 2016) - Zhang, Cheng; Zeng, Chuan-Chuan; Lai, Shang-Hai; Xing, De-Gang; Li, Wei; Han, Bing-Jie; Liu, Yun-Jun
Graphical abstract: Four new Ru(II) complexes [Ru(N-N)2 (Adbdp)] 2+ were synthesized and characterized. The in vitro cytotoxicity, apoptosis, cellular uptake, wound healing, cell cycle arrest, ROS and mitochondrial membrane potential, and western blot analysis were investigated. Abstract: A new ligand Adbdp and its four ruthenium(II) polypyridyl complexes [Ru(N-N)2 (Adbdp)](ClO4 )2 [N-N = dmb: 4, 4′-dimethyl-2, 2′-bipyridine1, bpy: 2, 2′-bipyridine2, phen: 1, 10-phenanthroline3 and dmp: 2, 9-dimethyl-1, 10-phenanthroline4, Adbdp = acenaphtheno[2, 3-b]-1, 4-diazabenzo[i]dipyrido[3, 2- a :2′, 3′- c ]phenazine] were synthesized and characterized by elemental analysis, ESI-MS and 1 H NMR. The cytotoxicity in vitro of the complexes against BEL-7402, HeLa, MG-63 and A549 cells was studied by MTT method. The IC50 values are 24.2 ± 1.9, 11.5 ± 3.6, 3.4 ± 0.3 and 9.7 ± 0.5 μM for complexes1, 2, 3 and4 toward A549 cells, respectively. The apoptosis was assayed with AO/EB and Hoechst 33258 staining methods. The cellular uptake was investigated with DAPI-stained cell nuclei. The reactive oxygen species and mitochondrial membrane potential were performed under fluorescent microscope. The cell cycle distribution was studied by flow cytometry and the protein expression of Bcl-2 family proteins was analyzed by western blot. The results show that the complexes induce A549 cell apoptosis through a ROS-mediated mitochondrial dysfunction pathway.